Islamic Religious Teacher Communication for Developing the Profile of Pancasila Students: A Case Study at MI al-Ma'arif 02 Malang Regency - Sholeh, Ahmad; Faizah, Maryam; Azizi, Alfan Nur (LP. Ma'arif Janggan Magetan, 2025)
The development of the Pancasila student profile within the Independent Learning framework requires effective communication between teachers and students to minimize misunderstandings. This study aims to explore and analyze the communication strategies employed by Islamic religious education teachers in shaping the dimensions of the Pancasila student profile. Using a case study approach at MI Al-Ma’arif 02, Malang Regency, data were collected through in-depth interviews, focus group discussions (FGDs), observations, and documentation. Data analysis followed the Miles and Huberman model, which includes data collection, data display, data condensation, and conclusion drawing/verification. The findings reveal that Islamic religious education teachers employ both individual and group communication approaches, utilizing technology-based media and involving parents to support the development of student character. The communication patterns include two-way communication through open class discussions, reflective activities, and ongoing guidance and monitoring, as well as collaborative communication through project-based learning, role-playing, and group work. In this process, Islamic religious education teachers function not only as educators but also as parental figures and peers. This research implies that there is a need for a program to develop communication for Islamic religious teachers so that the internalization of the values ​​of the Pancasila student profile dimensions in Islamic elementary education institutions is more effective and efficient.